2003
DOI: 10.1515/bc.2003.035
|View full text |Cite
|
Sign up to set email alerts
|

Protease Inhibitors Prevent Plasminogen-Mediated, But Not Pemphigus Vulgaris-Induced, Acantholysis in Human Epidermis

Abstract: Pemphigus is an autoimmune blistering disease of the skin and mucous membranes. It is caused by autoantibodies directed against desmosomes, which are the principal adhesion structures between epidermal keratinocytes. Binding of autoantibodies leads to the destruction of desmosomes resulting in the loss of cell-cell adhesion (acantholysis) and epidermal blisters. The plasminogen activator system has been implicated as a proteolytic effector in pemphigus. We have tested inhibitors of the plasminogen activator sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…These proteins are overexpressed in variety of malignancies, including breast, ovarian, glioma, and prostate cancers, and have been demonstrated to be essential in the maintenance of invasive and metastatic phenotypes (16). Several studies using in vitro and in vivo animal models have shown that either neutralizing uPA and/or uPAR function or blocking expression of these molecules significantly inhibits tumor invasion and metastasis in many cancers (5,(33)(34)(35)(36). Although both uPA and uPAR are widely implicated in prostate tumor progression, the extent of their interaction in relation to the tumorigenicity of prostate cancer is not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These proteins are overexpressed in variety of malignancies, including breast, ovarian, glioma, and prostate cancers, and have been demonstrated to be essential in the maintenance of invasive and metastatic phenotypes (16). Several studies using in vitro and in vivo animal models have shown that either neutralizing uPA and/or uPAR function or blocking expression of these molecules significantly inhibits tumor invasion and metastasis in many cancers (5,(33)(34)(35)(36). Although both uPA and uPAR are widely implicated in prostate tumor progression, the extent of their interaction in relation to the tumorigenicity of prostate cancer is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…This has proven particularly true for human prostate cancer cells, which form primary tumors and metastases with much lower efficiency when implanted ectopically in nude mice. Given that uPA and uPAR are frequently overexpressed in many cancers, uPA is considered a very important target molecule for cancer therapy (16,33,34). Recently, in vivo therapies that target uPA or uPAR in various cancers have been reported by several research groups (5,37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schuh et al . [29] tested inhibitors of the plasminogen activator system (anti-uPA, anti-tPA, anti-plasmin) with regard to their potential protective role. The authors found that these inhibitors failed to prevent PV-IgG mediated acantholysis, but acantholysis was effectively inhibited by the synthetic active site serine protease inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…The human organ culture model has been very valuable in obtaining information on the mechanisms of acantholysis and, moreover, has also been used to test old and new therapeutic drugs for pemphigus, for example, hydrocortisone [13], dapsone [13], methylprednisolone [17], and protease inhibitors [15]. Although most popular in the eighties, it is still used today, often in combination with other models [16, 2528].…”
Section: Organ Cultures Of Human Skinmentioning
confidence: 99%